2022
DOI: 10.1021/acs.est.2c02129
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Removal and Recovery of As(V) and As(III) from Strongly Acidic Wastewater by a UV/Formic Acid Process

Abstract: The removal of arsenic (As­(V) and As­(III)) from strongly acidic wastewater using traditional neutralization or sulfuration precipitation methods produces a large amount of arsenic-containing hazardous wastes, which poses a potential threat to the environment. In this study, an ultraviolet/formic acid (UV/HCOOH) process was proposed to reductively remove and recover arsenic from strongly acidic wastewater in the form of valuable elemental arsenic (As(0)) products to avoid the generation of hazardous wastes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The detailed photochemical parameters are elaborated in our prior work and Text S2. 23 The reactor, immersed in circulating cooling water, maintained a steady temperature of 25 ± 1 °C and was magnetically stirred at a rotational speed of 1500 r min −1 . This high rotational speed ensures homogeneity of the liquid phase during the reaction (Figure S2).…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…The detailed photochemical parameters are elaborated in our prior work and Text S2. 23 The reactor, immersed in circulating cooling water, maintained a steady temperature of 25 ± 1 °C and was magnetically stirred at a rotational speed of 1500 r min −1 . This high rotational speed ensures homogeneity of the liquid phase during the reaction (Figure S2).…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…9 In addition, because of the high metal content in the generated sludge, it is possible to recover valuable metals from the sulfide sludge. 10,11 Therefore, sulfide precipitation is one of the most suitable technologies for removing heavy metals from acidic wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…According to research by Kong et al [ 15 ], using UV light to accelerate the release of hydrogen sulfide from thiosulfate resulted in 99.9% of the arsenic being removed, and there was no hydrogen sulfide (H 2 S) pollution. To prevent the creation of hazardous waste, they devised a UV/formic acid (UV/HCOOH) technique for the reductive recovery of arsenic from extremely acidic wastewater in the form of a monolithic arsenic (As (0)) product [ 16 ]. These studies have shown positive findings for the removal of arsenic, but due to cost and process constraints, large-scale applications are difficult to implement.…”
Section: Introductionmentioning
confidence: 99%